Gossip, power and solidarity in Iranian men talk / Leila Mohajer - Leila, Mohajer (2013)
Gossip as a private, intimate talk is important in every society since it enhances solidarity and strengthens friendship. The studies on gossip are scarce specifically in the countries such as Iran where gossip is a forbidden activity. Moreover, gossip is attached to women speech as such; men try to avoid it in order to maintain their manhood. The motivation of this study is driven by the fact that in a patriarchal society like Iran, it is expected to observe power play in men speech and any feminine kind of talk like gossip is avoided to preserve their masculinity. This study investigates the way in which men gossip. It explores the functions of gossip and the manners in which Iranian men exert power and use solidarity when they gossip. Data of this study consist of audio-recorded face to face conversations of 12 Iranian men, forming four groups, which are transcribed based on a modified version of Jefferson‟s transcription convention (1979). Coates‟ gossip framework (2011a) is implemented in this study to investigate gossip and manifestation of power and solidarity. In the current study, conversation analysis (CA) is also used to analyze the conversation of the participants. For the purpose of data analysis, both qualitative and quantitative approaches are used. The overall findings suggest that Iranian men use language cooperatively when they gossip. They gossip about personal and private issues which are not only familiar but also generate common in-group interests. They consider gossip as an intimate activity because it strengthens their relationships. Linguistic features such as topic development, minimal responses, interruptions and epistemic modality are iv frequently used as a collaborative endeavor to build on each others‟ utterances and ultimately achieve solidarity. Another important finding is that power is embedded within cooperative talk amongst the Iranian men in this study. For example, power is frequently observed in high-handed arguments, some boastful comments and dominant interruptions. In summary, despite the embedded power in Iranian men talk, cooperative attitude is still prevailing and dominant. The male participants establish solidarity by gossiping in private domains and building on each other‟s utterances to strengthen their friendship. The cooperative attitudes observed among these Iranian men can be the result of the cultural changes in the society. Such changes may be due to the growing understanding about gender equal rights and especially among the young educated generation where patriarchy is not strongly practiced. This study reveals that although gossip is considered feminine, it can be practiced by men as well. This reaffirms the performativity of gender where people are able to perform and act in a way that is generally attached to the other gender (Cameron, 2011). This study also adds knowledge to the field of language and gender and contributes to the studies on male interaction in single sex groups.